2011
DOI: 10.1099/vir.0.031039-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete genomes of Camelus dromedarius papillomavirus types 1 and 2

Abstract: Camel papillomatosis has been described previously, but the genome of the suspected papillomavirus (PV) has not been identified. An outbreak of papillomatosis occurred in a dromedary farm of 55 animals in Sudan during August 2009. The disease was only present in young animals aged about 3-7 months, of which 44 % (11/25) were affected with lesions, mainly on the lips and lower jaw. This study reports for the first time the complete genomes of Camelus dromedarius papillomavirus types 1 (CdPV1) and 2 (CdPV2), iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
1
23
1
2
Order By: Relevance
“…The clinical sign, microscopic changes and gross lesions observed in the present study is well corroborated with the earlier reported data (Khalafala, 1998;Valentine, 2004;Ure 2011). Most of the cutaneous wart nodules caused by BPV-type 1 and 2 and confirmed to be positive for benign type by number of research workers (Bam et al, 2012;Pangry et al, 2010;Turk et al, 2005;Smith, 1990).…”
Section: Resultssupporting
confidence: 92%
“…The clinical sign, microscopic changes and gross lesions observed in the present study is well corroborated with the earlier reported data (Khalafala, 1998;Valentine, 2004;Ure 2011). Most of the cutaneous wart nodules caused by BPV-type 1 and 2 and confirmed to be positive for benign type by number of research workers (Bam et al, 2012;Pangry et al, 2010;Turk et al, 2005;Smith, 1990).…”
Section: Resultssupporting
confidence: 92%
“…We selected one pharyngeal and nine laryngeal HPV6-positive biopsy specimens (Table 1). In order to amplify the complete HPV6 genomes, automated DNA extraction (MagNA Pure LC total nucleic acid isolation; Roche) and long-range PCR (Expand Long Template PCR system; Roche) were performed (Table 2) (27). By using long PCR products as the templates, the complete genomic sequences were obtained by using 15 sequencing primers (Table 2).…”
mentioning
confidence: 99%
“…The first report of papillomatosis associated with PV in dromedaries was published in 1990 (Munz et al, 1990) and showed that dromedary camels in central Somalia aged 6 months to 2 years were primarily affected. Later, cases of papillomatosis in young dromedary camels have also been reported from Kenya (Dioli and Stimmelmayr, 1992), United Arab Emirates (Wernery and Kaaden, 1995) and Sudan (Khalafalla et al, 1998;Ure et al, 2011). PVs were found associated with a 2 kg wart-like growth on the right fetlock joint of a dromedary camel in India (Sadana et al, 1980) and a corneal papilloma mass in the left eye of a 15-year old dromedary male with a history of chronic severe keratoconjuctivitis (Kilic et al, 2010).…”
Section: Introductionmentioning
confidence: 99%